The association of plasma peroxiredoxin 3 with insulin in pregnant women - Wang, Li; Hao, Jun-Mei; Yu, Ai-Qun; Li, Tian-Tian; Liu, Ran-Ran; Li, Lianqin; Li, Jingmin; Li, Xiaoyan (Biochemical and biophysical research communications, 2019)
Peroxiredoxin 3 (PRX3) is predominantly located in mitochondria and plays a major role in scavenging hydrogen peroxide of mitochondria. In the present study, we detected plasma PRX3 in pregnant women receiving oral glucose tolerance test at 24–28 gestational weeks. Plasma PRX3 was significantly increased about 1 h later than insulin secretion. In vitro detection of PRX3 in mouse islet cells showed up-regulation by more than 2-fold at 1 h and reached its top at 2 h of glucose stimulation, and the PRX3 level in cultured mediums was concomitantly elevated in a glucose concentration-dependent manner. In addition, both fasting plasma insulin and PRX3 were significantly higher in the subjects of term pregnancy as compared to that at 24–28 gestational weeks, and there was a positive correlation between plasma PRX3 and insulin. Our results indicate that PRX3 plays an active role in the response to insulin release. The positive association of plasma PRX3 and insulin suggest PRX3 to be a potential indicator of high insulin resistance. •Plasma PRX3 and insulin are accordingly increased with gestational progression, which reaches the top at full term.•Plasma PRX3 is increased in the insulin releasing test, probably 1 h later than insulin secretion.•There is a positive correlation between fasting PRX3 and insulin in term pregnant women.•PRX3 levels in mouse islet cells and cultured mediums are concomitantly elevated in a glucose concentration-dependent manner.